2006
DOI: 10.1007/s11258-005-9023-1
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Studies on the Effects of Solar UV-B on bryophytes: Overview and Methodology

Abstract: In this review all recent field studies on the effects of UV-B radiation on bryophytes are discussed. In most of the studies fluorescent UV-B tubes are used to expose the vegetation to enhanced levels of UV-B radiation to simulate stratospheric ozone depletion. Other studies use screens to filter the UV-B part of the solar spectrum, thereby comparing ambient levels of UV-B with reduced UV-B levels, or analyse effects of natural variations in UV-B arising from stratospheric ozone depletion. Nearly all studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…While UV‐B‐screening compounds and structures are a feature of the epidermal layers of many higher plants, the simple structure of bryophytes, particularly the lack of epidermal layers, was assumed to render them particularly vulnerable to UV‐B damage (Gwynn‐Jones et al , 1999). However, recent work suggests that some bryophyte species have high resilience to UV‐B radiation (Lud et al , 2002; Newsham et al , 2002; Newsham, 2003; Boelen et al , 2006; Dunn & Robinson, 2006; Clarke & Robinson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While UV‐B‐screening compounds and structures are a feature of the epidermal layers of many higher plants, the simple structure of bryophytes, particularly the lack of epidermal layers, was assumed to render them particularly vulnerable to UV‐B damage (Gwynn‐Jones et al , 1999). However, recent work suggests that some bryophyte species have high resilience to UV‐B radiation (Lud et al , 2002; Newsham et al , 2002; Newsham, 2003; Boelen et al , 2006; Dunn & Robinson, 2006; Clarke & Robinson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of influence was expected for attributes a priori neutral for UVACs, such as size, life‐form, sex, reaction‐pH (R) or nitrogen (N), but not for attributes presumably influencing the light levels (and thus, the UV levels) received by the bryophytes, such as orientation, light (L), exposure index or biogeographic origin. Nevertheless, it must be taken into account that a UV increase has sometimes resulted in a concomitant UVACs increase in bryophytes under field conditions (Newsham, ; Newsham, Geissler, Nicolson, Peat, & Lewis‐Smith, ; Newsham & Robinson, ; Núñez‐Olivera, Otero, Tomás, Fabón, & Martínez‐Abaigar, ; Núñez‐Olivera, Otero, Tomás, & Martínez‐Abaigar, ), though this is not always the case (Arróniz‐Crespo et al., ; Boelen, De Boer, De Bakker, & Rozema, ; Núñez‐Olivera et al., ; Robinson, Turnbull, & Lovelock, ; Snell, Convey, & Newsham, ). The non‐influence of light‐related attributes on UVACs that was revealed in our study, together with the contrasting responses of UVACs to UV radiation found in the literature, suggest that UVACs may be notably constitutive for each bryophyte species or lineage, and not especially inducible by the environment (Martínez‐Abaigar & Núñez‐Olivera, ; Robinson & Waterman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our aim was to study the structure and function of UVR8 from the moss P. patens and the liverwort Marchantia polymorpha . The rationale for studying UVR8 in these two species is that: they represent two early diverging evolutionary lineages of land plants that were important for land colonisation, a process in which UV‐B radiation could play a role as an evolutionary pressure; liverworts and mosses may represent two different modalities of bryophytes in their responses to UV‐B radiation (Fabón et al ., ); responses of bryophytes to UV‐B radiation depend on the species used (Boelen et al ., ; Martínez‐Abaigar & Núñez‐Olivera, ), so that using two different species can allow, to a certain extent, assessment of the variability of UVR8 behaviour in bryophytes; and the two species studied are increasingly important as model species in plant biology.…”
Section: Introductionmentioning
confidence: 99%